Levels of Selected Persistent Organic Pollutants in Human Milk Samples from Bosnia and Herzegovina - Lugušić, Aida; Porobić, Aleksandra; Muratović, Samija; Djedjibegović, Jasmina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2026)
One of the greatest challenges of today is environmental pollution, which leads to serious threats to human health and the entire ecosystem. Due to their high persistence and low biodegradability, polychlorinated biphenyls (PCBs) and organochlorinated pesticides (OCPs), as the main categories of environmental pollutants of anthropogenic origin, remain present in the environment for a long period of time, continuously circulating between air, water and soil, posing a permanent risk to public health. Bosnia and Herzegovina has not previously conducted studies on the presence of environmental pollutants in breast milk, the results of which could contribute to more effective public health protection and serve as a basis for strategic planning aimed at reducing exposure to environmental pollutants. For this reason, the aim of this study was to determine the levels of selected persistent organic pollutants (PCBs and OCPs) in breast milk of lactating women (N=67) from Bosnia and Herzegovina (Federation of Bosnia and Herzegovina, Republika Srpska and Brčko District). The results presented here are the first of their kind for the territory of our country. The average values of quantified concentrations of PCB (17 congeners) and OCP (8 compounds) ranged from 1.03-162.29 ng/g l.w. and from 0.27 to 14.64 ng/g l.w., respectively. PCB congeners 52, 77, 126, and 169 were detected at higher levels compared to those reported in some of the European and Asian countries. In Brčko District and Republika Srpska, higher values were found compared to the Federation of Bosnia and Herzegovina.The measured concentrations of selected persistent pollutants in breast milk samples collected in Bosnia and Herzegovina mostly correspond to the literature data from similar studies conducted in the countries of the region and Europe.